Regulatory effects of C5a on IL-17A, IL-17F, and IL-23 - Grailer, Jamison J.; Bosmann, Markus; Ward, Peter A. (Frontiers in Immunology, 2013)
The complement anaphylatoxin, C5a, through binding to its receptors (C5aR or C5L2), has important biological properties for recruitment and activation of phagocytes. C5a has been identified as a powerful modulator of Toll-like receptor-induced cytokine and chemokine production by macrophages. Both the complement system and the interleukin (IL)-17 cytokine family protect against extracellular pathogens by enhancing innate immune functions. On the basis of its concentration, C5a can either positively or negatively modulate the production by macrophages of IL-17 family members as well as IL-23 via the phosphatidylinositol 3-kinase/Akt signaling cascade. C5a can also affect the production and maintenance of IL-17-producing T cells. Using C5a, C5aR, or C5L2 deficiency or blockade, IL-17/IL-23 production and/or IL-17-dependent disease progression has been shown to be substantially modified. The contributions of C5a interaction with its receptors in the production of IL-17/IL-23 and promotion of IL-17-dependent immune responses are reviewed.